Promoting Healthy Lifestyles Among The Indonesian Academic Community In Thailand To Prevent Non-Communicable Diseases (NCDS) - Pramono, Ardi (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Non-communicable diseases (NCDs) are one of the leading causes of death in the world, including Indonesia. Non-communicable diseases (NCDs) such as diabetes mellitus, hypertension, heart disease, cancer, stroke, and mental health disorders are increasingly being found in young people or adolescents. Lack of knowledge in adolescents causes risk factors for unhealthy lifestyles in adolescents. This community service will explore the problem of non-communicable diseases in Indonesian students studying in Thailand, through brave lecture activities and surveys. The survey results showed that the subjects' awareness of healthy living practices was moderate. More than 50% of respondents avoided consuming sweet foods regularly and did physical activity at least once a week. However, several behavioral patterns need to be watched out for, especially the high percentage (35%) of respondents who used laptops for more than six hours every day which resulted in a sedentary lifestyle and musculoskeletal problems.